Inequities in the emergence, manifestations and consequences of COVID19 (Colombia Medica, 2021)
The Inequality Virus is the name given to SARS-COV2 by an OXFAM publication, highlighting that during the pandemic, the ten richest men on the planet have earned 540 billion dollars, a figure that would serve to finance a universal vaccine for COVID19. This fact is an exemplary demonstration of the inequities of the pandemic, analyzed below in three different dimensions: 1) The origins of the pandemic, in the context of inequitable socio-ecological systems where the relationship amongst humans and between humans and nature has been broken; 2) Its manifestations, in conditions of social inequity, with its patterns of occurrence and a painful trace of disease and death; and 3) The consequences, in a vicious circle with the complex systems that gave rise to it, causing a profound situation of inequity, in other words, the pandemic as a source of more unjust differences.